Dose response of neural mobilization on hamstring flexibility in patients with non-specific low back pain: a randomized control trial - Rabia Liaqat; Aneela Zia (The Rehabilitation Journal, 2025)
Background: Non-specific low back pain (NSLBP) often correlates with reduced hamstring flexibility, contributing to altered biomechanics and recurrent symptoms. Neural mobilization (NM) techniques are increasingly integrated into management strategies to address neurogenic inflammation and neural tissue mobility. However, the dose-response relationship of NM for hamstring flexibility remains unclear, with limited studies isolating dosage effects amid multimodal interventions.